Diffusion brazing repair of IN738 superalloy with crack-like defect: microstructure and tensile properties at high temperatures. (2nd January 2019) - Ye, Y.; Zou, G.; Long, W.; Jia, Q.; Bai, H.; Wu, A.; Liu, L.
ABSTRACT: In this study, tapered slots with an opening width about 200 μm were artificially fabricated in IN738LC superalloy to imitate service cracks. The 'cracks' were repaired by diffusion brazing with a Ni–Cr–Co–Al–Ta–B filler alloy at 1150°C and then heat treated at 1180°C (HT-A) and 1190°C (HT-B), respectively. A joint with uniform microstructure, chemical composition and hardness was obtained using HT-B. The mechanisms of the borides evolution during homogenisation were discussed. The tensile strength of the HT-B joint tested at 20, 600 and 800°C reached up to approximately 96, 90 and 87% of the base metal, respectively. The fracture modes of the joints tensile tested at various temperatures were discussed.